Der griechisch-orientalische Religionsfonds der Bukowina 1783-1949 Kontinuitäten und Brüche einer prägenden Institution des Josephinismus - Scharr, Kurt (2020)
In the course of the Josephinian reforms, monasteries were dissolved and church property was fundamentally transformed. At that time, Bukovina was still a young province of the Habsburg Empire. The Orthodox Church dominated denominationally. As early as 1783, a Greek-Oriental religious fund was created based on the church property. This institution was fundamentally different from Catholic funds, since it was regionally anchored from the start. As the largest landowner of Bukovina, this institution developed into a factor that shaped the region and society significantly until it was dissolved in 1949. The analysis of the Bukovinian Religious Fund in its importance for the design, development and nationalization of the region as part of the Habsburg monarchy as well as Greater Romania is the subject of the monograph. It offers a surprisingly new insight into a neglected research field, far beyond the region.